The expansion of community kitchens in contemporary Argentina: the images that reflect the mirror - Magliano, María José (2025)
The article analyzes the expansion of community kitchens in contemporary Argentina as a response to broader socio-economic processes linked to increasing poverty and social exclusion in urban contexts. It is based on a qualitative methodology that combines individual research carried out in popular neighborhoods in the city of Cordoba with a migrant population, and a collective study developed in the same city with women who lead community kitchens. The main findings show, on the one hand, the persistent difficulties encountered by low-income families (natives and migrants) to ensure their subsistence and, on the other hand, the forms of collective organization that are emerging from the urban margins to generate more dignified life sustainability strategies.